Acute effects of customizing a tennis racket on serve speed - Sögüt, M. (Baltic Journal of Sport and Health Sciences, 2017)
Background. A vast number of tennis players use additional lead weights attached to their rackets in order to improve stroke performances. However, there is limited evidence that racket customization as such boosts efficiency in different age and performance levels. The purpose of this repeated measures design study was to determine the acute effects of adding weight to the tip of a racket on serve speed in tennis players. Methods. Participants were male tennis players from three different age and performance levels: elite junior (n = 7, age = 15.71 ± 0.95 years), colligate (n = 11, age = 22.36 ± 2.54 years), and senior recreational (n = 17, age = 52.94 ± 9.43 years). Three identical rackets, two of which were customized by adding ten and twenty gram lead weights on the tips, were used for the measurements. A radar gun was utilized to assess serve speed of the participants. Results. The repeated measures ANOVA results revealed no significant differences among serve speed scores for the three conditions in each group. Conclusion. Results suggest that customizing a tennis racket by adding lead weight to the tip might not necessarily yield differences in serve speeds in tennis players from different age and performance levels. (Abstract)